Childhood asthma - M. Levin; E. Weinberg (South African Family Practice)
Asthma is the most common chronic disease of South African children, affecting growth and development and quality of life. Features supporting the diagnosis are a family or personal history of atopy, night cough, exercise-induced cough and/or wheeze and seasonal variation in symptoms. Asthma is on the increase in both developed and developing countries, in both rural and urban communities. The first part of this series aims to give a brief overview of the epidemiology, pathophysiology and diagnosis of childhood asthma.